A Comparative study on secure routing algorithms SAODV and A-SAODV in Mobile AdHoc Networks (MANET) – The Enhancements of AODV - RAJESHWAR, JARUPULA; NARSIMHA, Dr G (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
A freely moving nodes forming as group to communicate among themselves are called as Mobile AdHoc Networks (MANET). Many applications are choosing this MANET for effective commutation due to its flexible nature in forming a network. But due to its openness characteristics it is posing many security challenges. As it has highly dynamic network topology security for routing is playing a major role. We have very good routing protocols for route discovery as well as for transporting data packers but most of them lack the feature of security like AODV. In this paper we are studying the basic protocol AODV and identify how it can be made secure. We are studying a protocol S-AODV which is a security extension of AODV which is called Secure AODV (S-AODV) and we are studying enhanced version of S-AODV routing protocol a Adaptive Secure AODV (A-SAODV). Finally we have described about the parameter to be taken for performance evaluation of different secure routing protocols